2021
DOI: 10.1109/tmi.2021.3076191
|View full text |Cite
|
Sign up to set email alerts
|

MDPET: A Unified Motion Correction and Denoising Adversarial Network for Low-Dose Gated PET

Abstract: In positron emission tomography (PET), gating is commonly utilized to reduce respiratory motion blurring and to facilitate motion correction methods. In application where low-dose gated PET is useful, reducing injection dose causes increased noise levels in gated images that could corrupt motion estimation and subsequent corrections, leading to inferior image quality. To address these issues, we propose MDPET, a unified motion correction and denoising adversarial network for generating motion-compensated low-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, the number of institutions could be more than three with more diverse low-dose settings. For example, Kaplan and Zhu [5], Ladefoged et al [50], and Zhou et al [51] used a 10%-count low-dose setting. Wang et al [3] and Whiteley et al [52] deployed a 25%-count low-dose setting, while Ouyang et al [9] considered a 1%count ultralow-dose setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of institutions could be more than three with more diverse low-dose settings. For example, Kaplan and Zhu [5], Ladefoged et al [50], and Zhou et al [51] used a 10%-count low-dose setting. Wang et al [3] and Whiteley et al [52] deployed a 25%-count low-dose setting, while Ouyang et al [9] considered a 1%count ultralow-dose setting.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al. [25] proposed a unified motion correction and denoising adversarial network for generating motion‐compensated low noise images from low‐dose gated PET data. In recent years, Kupyn et al.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results showed that their model can generate images conditioned on class labels. Zhou et al [25] proposed a unified motion correction and denoising adversarial network for generating motion-compensated low noise images from low-dose gated PET data. In recent years, Kupyn et al proposed a deblurring Gan model named Deblur-Gan [26], which trains a recovery image generator using CNN technology and a discriminant network patchGan, and the loss function is composed of the counter loss and content loss.…”
Section: Related Workmentioning
confidence: 99%
“…al. 15 , also proposed a unified motion correction and denoising deep framework for low-dose gated PET. In our work, we implemented a direct motion correction framework in imagedomain based on U-Net architecture without the need to access PET raw data.…”
Section: Introductionmentioning
confidence: 99%